2000
DOI: 10.1182/blood.v95.12.3986
|View full text |Cite
|
Sign up to set email alerts
|

Detection of active hepatitis C virus and hepatitis G virus/GB virus C replication in bone marrow in human subjects

Abstract: We have analyzed the presence of hepatitis C virus (HCV) and hepatitis G virus (HGV) sequences in bone marrow and serum samples from 48 patients of a hematologic outpatient clinic. HCV RNA was detected in 18 (38%) and 15 (31%) and HGV RNA was detected in 6 (13%) and 9 (19%) of serum and bone marrow samples, respectively. In 3 patients, HGV RNA was detectable in bone marrow but not in the serum; 2 of these patients were negative for the presence of specific antibodies. Using a highly strand-specific Tth-based r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(25 citation statements)
references
References 24 publications
2
21
0
1
Order By: Relevance
“…However, the clinical and biological consequences of extra‐hepatic replication are not clearly understood. Chronic Hepatitis C (CHC) infection is associated with several extra‐hepatic manifestations including cutaneous vasculitis, glomerulonephritis, neuropathy, lymphoproliferative, and CNS disorders [Radkowski et al, 2000; Blackard et al, 2006]. Given that CHC infection results in an increase in lymphoproliferative and autoimmune disorders, extra‐hepatic HCV replication could potentially contribute to the pathogenesis of these complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical and biological consequences of extra‐hepatic replication are not clearly understood. Chronic Hepatitis C (CHC) infection is associated with several extra‐hepatic manifestations including cutaneous vasculitis, glomerulonephritis, neuropathy, lymphoproliferative, and CNS disorders [Radkowski et al, 2000; Blackard et al, 2006]. Given that CHC infection results in an increase in lymphoproliferative and autoimmune disorders, extra‐hepatic HCV replication could potentially contribute to the pathogenesis of these complications.…”
Section: Discussionmentioning
confidence: 99%
“…75,76 However, most groups have not been able to detect antisense RNA in liver biopsies, suggesting that GBV-C is not a hepatotropic virus. [77][78][79][80] Comparisons between GBV-C and HCV RNA concentrations in plasma and liver tissue found that HCV RNA is predominantly present in liver tissue, whereas GBV-C RNA is predominantly in plasma, suggesting that HCV replicates in the liver and GBV-C does not. 79 In one study, both positive-and negative-strand RNA were demonstrated in peripheral blood mononuclear cells (PBMCs), bone marrow, and spleen, leading to the conclusion that GBV-C is primarily a lymphotropic virus.…”
Section: Virology: Gbv-c and Hcv Comparisonsmentioning
confidence: 99%
“…[77][78][79][80] Comparisons between GBV-C and HCV RNA concentrations in plasma and liver tissue found that HCV RNA is predominantly present in liver tissue, whereas GBV-C RNA is predominantly in plasma, suggesting that HCV replicates in the liver and GBV-C does not. 79 In one study, both positive-and negative-strand RNA were demonstrated in peripheral blood mononuclear cells (PBMCs), bone marrow, and spleen, leading to the conclusion that GBV-C is primarily a lymphotropic virus. 12,39,41,78,79,81,82 We developed an infectious molecular clone of GBV-C and found that it replicated primarily in CD4+ T cells, 12,83 confirming that this virus is able to replicate in lympho-cytes.…”
Section: Virology: Gbv-c and Hcv Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negativestrand HGV RNA has been amplified by polymerase chain reaction (PCR) from peripheral blood mononuclear cells. CD4+ T cells, bone marrow, lymph node, and spleen at lower levels in liver [5][6][7][8][9]. Diagnosis of HGV viremia is mainly by PCR.…”
Section: Introductionmentioning
confidence: 99%